Proximal Femoral Nail Failures in Extracapsular Fractures of the Hip - MSG Ballal (Journal of Orthopaedic Surgery, 2008)
Purpose. To review patients with proximal femoral nails (PFNs) in our hospital that developed complications and needed revision. Methods. Between January 2000 and June 2006, records of 216 patients with PFN fixations for traumatic extracapsular trochanteric fractures (n=160), pathological fractures (n=23), and as a prophylactic measure for metastasis (n=33) were retrospectively reviewed. The injury mechanism, reduction technique and quality, and time to and cause of implant failure were recorded. Results. 12 PFNs failed: 8 in the trauma group, 3 in the pathological group, and one in the prophylactic nailing group. Two PFNs broke at the proximal lag screw level at a later stage secondary to non-union of the pathological fractures. One broke at the level of the distal locking screw at an early stage, as the locking holes were too close to the fracture. Conclusion. Poorly reduced fractures tend to fail early, whereas late failures are due to non-union. Good reduction with minimal dissection, the use of appropriate nail length, and proper positioning of the nail and screws are necessary to avoid failure or revision.